Evaluation of mixtures of clay for the manufacture of refractory bricks used for the conversion technology of used ovens in North Santander (Revista de Investigaciones Universidad del Quindío, 2014)
The physical (ceramic aptitude) and chemical (X-ray fluorescence) properties of four raw materials were analyzed (Peracos clay, La Alejandra clay, Kaolin HS-801 A and mixes Táchira). Measurement indicators were obtained through the studied temperatures (1150 and 1280 ºC) to identify its composition and the individual behavior; and select the amounts to be used in the formulation of the different mixtures: MA, MB, MC, MD, ME and MF. Finally, the most appropriate mixtures for the manufacture of a refractory brick prototype were used to real scale. The mixture MA presented a low percentage of contraction in stew of 2.89 at the temperature of 1280 ºC, a constant apparent density of 1,60g/cm3 and resistance to the break of 16.98Kgf/cm2. MB presented a low percentage of contraction in stew of 5.69 to the temperature of 1280 ºC, an apparent density of 1.58g/cm3 and a resistance to the break of 49. 01 Kgf/cm2, and ME presented a low percentage of contraction in stew of 5,88 to the temperatureof 1280 ºC, an apparent density of 0.93g/cm3 and a resistance to the break of 7,68Kgf/cm2; those that fulfill the conditions required by NTC 623 for the refractory brick manufacture.
Keywords: Clay; Kaolin; refractory brick; characterization of raw materials